Computer-based decision support system (DSS) application in transportation sector: A review - Ibrahim, Muhammad Shafiq; Kamat, Seri Rahayu; Shamsuddin, Syamimi (Academia Industry Networks, 2023)
Poor planning in urban transport infrastructure causes severe congestion, pollution and stifles city productivity. Recently, computer-based decision support systems (DSS) that can solve several transportation decision problems have gained popularity. This paper concisely reviews the application and contribution of existing research of DSS for the transportation sector. A thorough systematic literature review (SLR) was employed to find relevant material using web search engines like Scopus, Google Scholar and Web Science. The currently available DSS are separated into two categories: (i) developed DSS primarily for research publication and (ii) established web-based DSS that are available online. Most of the latest DSS for research publication within 2017 and 2022 are more focused on public transportation management, road safety and hazardous materials transportation. It is found that existing web-based DSS apps available online, are not focused on efforts to avoid the variables that cause traffic accidents. Most systems only provide limited access to information about road safety issues and concerns. The survey found no research on DSS development, notably in addressing traffic accident causes such driver fatigue. As a result, a decision support system should be built that will monitor and detect the driver's fatigue level, provide a warning, make a judgement about the driver's current position, and recommend a solution whether the driver is safe to drive or not. This study will help academics, policymakers, and practitioners identify research gaps, future directions, and viable areas for multiple-criteria DSS in transportation.